Implementar el sistema de gestión de seguridad y salud en el trabajo teniendo en cuenta el decreto 1072 del 2015, el decreto 52 del 2017 y la resolución 1111 del 2017 en el supermercado Mercarapido Nani (2019)
The objective of this work is to implement the (SG-SST) Occupational Health and Safety Management System under the requirements of Decree 1072 of 2015, Decree 052 of 2017 and Resolution 1111 of 2017 which was repealed by Resolution 0312 of 2019 all this for the company Mercarapido Nani since it needs to comply with the guidelines required by the government and also the company wants to provide its workers a job in which they do not take risks to those who are exposed in their daily lives either mitigating or eliminating them, generating an apt workspace in which the workers feel comfortable with their safety. The work of degree began with an initial diagnosis of the company to know in what situation was facing the requirements of the government being evaluated the company with the matrix of minimum requirements provided by Resolution 1111 of 2017, after this the legal matrix which helps to identify which rules, laws and decrees govern the company against occupational safety and health, afterwards the inspection of the company and its places of work was done in order to make the matrix of hazard identification and risk mitigation in which the risks to which the workers are exposed were identified and assessed.